The clinical and immune outcomes after food allergen immunotherapy emphasizing the development of tolerance. Issue 6 (December 2019) - Miller, Jennifer M.; Davis, Carla M.; Anvari, Sara
Abstract : Purpose of review: The present review serves to outline the direction of food allergy immunotherapy research with an emphasis on clinical and immunologic outcomes. It helps to delineate sustained unresponsiveness achieved from food immunotherapy as the clinical outcome most similar to immune tolerance. Recent findings: We will discuss the difference between immune tolerance, desensitization, and sustained unresponsiveness in relation to food immunotherapy by discussing the clinical and immunologic changes which have been recently discovered. Summary: Research has recently shown that oral immunotherapy is most efficacious clinically at achieving desensitization to a food and sustained unresponsiveness.